Buying In: Big-Time Women's College Basketball and the Future of College Sports - Miller, Aaron L. (Rowman & Littlefield Publishers, 2022)
Buying In: Big-Time Women’s College Basketball and the Future of College Sports juxtaposes the rise of women’s college sports with the historical transformations that set the stage for contemporary big-time college sports. Aaron Miller draws on positive psychology to create a new framework he calls “positive anthropology.” He uses this lens to highlight the accomplishments of women’s college basketball teams and engages with college athlete exploitation, pay-for-play, and other contemporaneous issues that affect both women’s and men’s teams, though women’s teams are often excluded from the popular conversation. With insights drawn from – and applicable to – a wide range of scholarly fields in the humanistic social sciences, this book will be of particular interest to scholars, researchers and educators working in the fields of sports studies, gender studies, education, sociology, history, and anthropology, as well as anyone interested in the future of big-time college sport and higher education. This book poses and answers the question: “How can scholars help envision a brighter future for all college athletes, male and female?”